Genetic Association between Matrix Metalloproteinases Gene Polymorphisms and Risk of Prostate Cancer: A Meta-Analysis - Weng, Hong; Zeng, Xian-Tao; Wang, Xing-Huan; Liu, Tong-Zu; He, Da-Lin (Frontiers in Physiology, 2017)
Background and Objective: Studies suggests that matrix metalloproteinase (MMP)-2 -1306 C/T and MMP-1 -1607 1G/2G polymorphisms affect the risk of prostate cancer. However, the conclusions remain controversial and no pooled evidence of this topic has been published. Therefore, we aimed to perform a meta-analysis to shed some light on the controversial conclusion pertaining to the associations of MMP-2 -1306 C/T and MMP-1 -1607 1G/2G polymorphisms with prostate cancer susceptibility. Methods: A thorough literature search was performed up to August, 2016 with the PubMed, EMBASE, CBM, CNKI, and Wanfang databases. Odds ratios (ORs) and corresponding 95% confidence intervals (95%CIs) were calculated to address the correlations between these polymorphisms and risk of prostate cancer. Results: The meta-analysis included six studies (1921 patients and 1988 controls) on MMP-2 -1306 C/T polymorphism and three studies on MMP-1 -1607 1G/2G polymorphism (438 patients and 394 controls), respectively. The overall results of meta-analysis showed that an elevated risk of the disease was implicated inMMP-2 -1306 C/T polymorphism under two genetic models (CT vs. CC: OR = 1.78, 95% CI = 1.33-2.38; TT+CT vs. CC: OR = 1.62, 95% CI = 1.24-2.12) and no significant association was observed between MMP-1 -1607 1G/2G polymorphism and the risk of prostate cancer. The subgroup analysis results of MMP-2 -1306 C/T polymorphism were similar to the overall results. However, decreased risk of prostate cancer was observed in the Caucasians for MMP-1 -1607 1G/2G polymorphism. Conclusions: Current meta-analysis indicates that MMP-2 -1306 C/T polymorphism is associated with elevated risk of prostate cancer, but MMP-1 -1607 1G/2G polymorphism may inhibit the occurrence of prostate cancer in Caucasians. Further studies are warranted to verify the conclusions.